P243 Anxiety and depression in adolescents and adults with cystic fibrosis. (2nd December 2011) - Fainardi, V; Iacinti, E; Longo, F; Tripodi, M C; Pisi, G
Abstract : Background: Little is currently known about the anxiety and depression co-morbidities and Cystic Fibrosis (CF). Aim: To evaluate the association between anxiety and depression and long-term treatment burden in CF patients. Subjects and Methods: In 82 CF patients (36 males, age range 12–44 years, BMI range 15–29 kg/m 2 ), anxiety and depression were assessed by the Hospital Anxiety Depression Scale (HADS). In all patients, spirometry and current therapy, such as scheduled intravenous antibiotics, chronic use of aerosolized antibiotics, insulin therapy, pancreatic enzymes and long-term oxygen therapy, were recorded. Results: A wide range of airflow obstruction was found (FEV1 range 26–129% pred). 54, 68, 12, 85, and 11 patients underwent intravenous antibiotics, aerosolized antibiotics, insulin therapy, pancreatic enzymes and long-term oxygen therapy, respectively. 33 (40%) and 15 (18%) out of 82 patients were respectively anxious and depressive. Depression was significantly associated with intravenous antibiotics (p<0.01, OR 6.0, CI 0.9 to 41) and with long-term oxygen therapy (p<0.01, OR 1.4, CI 0.9 to 1.9). Conclusions: The present study shows that use of scheduled intravenous antibiotics and long-term oxygen therapy significantly affect psychological functioning profile in adolescents and adults with CF. Our results further suggest the value of psychological support in CF patients with advanced lung disease.